Comparison of acute kidney injury after zero ischemia robot-assisted partial nephrectomy versus open and laparoscopic partial nephrectomy in patients with renal mass (Annals of Medical Research, 2021)
Aim: Robotic assisted laparoscopic partial nephrectomy (RALPN) is promising option for RCC treatment with favorable outcomes. In this present study we aimed to compare the incidence of (AKI) acute kidney injury measured by AKIN (Acute Kidney Injury Network) criteria between open partial nephrectomy (OPN), laparoscopic partial nephrectomy (LPN) and RALPN procedures with zero ischemia periods. Material and Methods: The medical records of 88 patients with renal mass who underwent OPN, LPN and RALPN at our institution [24 female/64 male; median age of 55 (IQR: 46–65) years] were evaluated retrospectively. AKI was defined by AKIN criteria. Results: Twenty-six patients underwent OPN, 32 LPN and 30 patients RALPN. Mean preoperative creatinine was 0.92 ±0.43 mg/dl, mean hemoglobin level was 14.0±1.9 g/dl. Total of 19 patients developed AKI according to the AKIN criteria, all of those had stage 1 AKI, 10 (53%) in OPN, 7 (3%) in LPN and 2 (11%) in RALPN group (p=0,004). Multivariate regression analysis adjusted by age and gender showed that operation time per minute [1.02 (CI 95%, 1.00, 1.04) p=0.04], fluid administered as ml/kg/hour [1.003 (CI 95%, 1.000, 1.006) p=0.04], red blood cell transfused as unit [1.27 (CI 95%, 1.07, 1.52) p=0.006] and operation type as RALPN surgery versus OPN and LPN [0.11 (CI 95%, 0.02, 0.58) p=0.01] were significantly associated with development ıf AKI.Conclusion: Robot assisted partial nephrectomy is more favorable approach compared to OPN and LPN with lower operation time and lower hemoglobin loss.